Implementation of Management of Slum Settlement in Cities, Review of Slum Settlement Problems in Indonesia (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Eliminating the problem of slum settlements is one of the efforts to achieve development goals in today's world. This is one of the goals to be achieved for the benefit of humans and nature. It is important to know the various efforts to solve the problem of slum settlements in order to get the maximum results and the target according to the characteristics of each area. The literature review method this time is a systematic review method where the authors classify various methods and approaches in handling slum problems in Indonesia. The purpose of this review article is to find out various kinds of approaches or methods in dealing with the problem of urban slum settlements in Indonesia. Based on the above objectives, the problem can be formulated, what are the methods which are handling urban slum settlement problems in Indonesia. This review article uses literature studies and then synthesizes it by reading, understanding and analyzing the information conveyed by the authors in the concepts they put forward. The result is a grouping of various methods in dealing with the problem of slum settlements. Key Word : Implementation; Urban; Slums Abstrak :   Menghilangkan permasalahan permukiman kumuh merupakan salah satu upaya untuk mewujudkan tujuan pembangunan di dunia sekarang ini. Hal ini merupakan salah satu tujuan yang ingin dicapai untuk kemaslahatan manusia dan alam. Berbagai upaya penyelesaian permasalahan permukiman kumuh menjadi penting untuk diketahui agar mendapatkan hasil yang maksimal dan tepat sasaran sesuai karakteristik masing-masing wilayah. Metode review literatur kali ini adalah metode systematic review dimana penulis mengelompokkan berbagai metode dan pendekatan dalam penanganan permasalahan kumuh di Indonesia. Tujuan dari review artikel ini adalah mengetahui berbagai macam pendekatan atau metode dalam rangka penanganan masalah permukiman kumuh di perkotaan di Indonesia. Berdasarkan dari tujuan diatas dapat dirumuskan permasalahan yaitu apa saja metode penanganan permasalahan permukiman kumuh diperkotaan yang ada di Indonesia. Review artikel ini menggunakan studi literature kemudian melakukan sintesis dengan cara membaca, memahami dan menganalisis informasi yang disampaikan oleh penulis dalam konsep yang mereka kemukakan. Hasilnya adalah terdapat pengelompokan berbagai macam metode dalam menangani permasalahan permukiman kumuh.   Kata Kunci:    Implementasi; Perkotaan; Permukiman Kumuh;